Morfogênese e calogênese in vitro em jenipapeiro (Genipa americana L.) - Oliveira, Annie Carolina Araújo de (2016)
Plant tissue culture has shown to be effective in multiplication and conservation of plant genetic resources. The genipap (Genipa americana L.), from the Rubiaceae family stands out for its plurality of uses, either as a forest species, fruit production or in traditional medicine. This study was divided into two parts. The first study investigated the effects of NAA concentrations (0.0, 0.2, 0.4 and 0.6 mg L-1) in combination with 1.0 mg L-1 of BAP in the morphogenesis of genipap zygotic embryos and embryonic axis of Núcleo Bandeirante (NB) access. At 30 days, it was observed that the in vitro regeneration of genipap is possible from the conversion of whole embryos in a medium supplemented with 0.6 mg L-1 NAA. The largest shoot length, number of leaves and roots were obtained in the medium NAA free. The progressive increase in the concentration of NAA induced the formation of compact calli, especially in the embryonic axis segment. Regeneration via direct organogenesis was not observed. The second part aimed to determine the effect of 2,4-D (0.0, 2.0, 4.0, 6.0 and 8.0 mg L-1) for induction of callus from leaf and nodal explants of genipap and characterize the dynamics of kinetics growth. The best induction response occurred at a concentration of 2.0 mg L-1 2,4-D and 1.77 mg L-1 BAP for leaf explants of NB, SA and SAL accesses, with emphasis on access SA who presented a biomass of 0.2223 g after 60 days of cultivation. However, for callus obtained from nodal segments, the response due to 2,4-D was different between the accesses. The fresh weight increase was higher for NB and SA at concentration 4.0 mg L-1 2,4-D and SAL, at 2.0 mg L-1 2,4-D. The kinetics growth was established from the fresh weight of callus at intervals of 10 days. The growth curve of leaf and nodal explants callus showed a linear pattern and only three stages of growth were observed: lag, exponential and linear. Calli of SA nodal segment should be transferred to a new culture medium after 40 days of cultivation.